McSweyn, Margarita Salazar (audio interview #2 of 3) - McSweyn, Margarita Salazar (b. 7/20/1916 - d. 8/22/1989); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the second of three interviews with Margarita Salazar McSweyn conducted in the living room of her small, comfortable home in East Los Angeles. As before, she seemed to enjoy the interview process, although she became rather subdued and sad in talking about her brother's death. This interview covers her defense work at Lockheed during the war. The overall audio quality of this interview is good although there are technical problem on the first sides of the tapes. 11/3/1980